Strategic management of privatization: a framework for planning and implementation - Rondinelli, Dennis A.; Iacono, Max (1996)
The continuing interest of governments around the world in privatizing state-owned enterprises (SOEs) is making privatization policy an important instrument for promoting market-oriented approaches to economic development. Privatization has become an integral part of administrative reform in former centrally planned socialist economies, developing countries, and post-industrial societies. More than a decade of experience with privatization provides lessons that can help governments to plan, implement and manage the process more efficiently, effectively, and responsively. The framework for managing privatization described here draws from lessons of that experience to define the forms, scope and pace of privatization, choose organizational structures for management, identify macropolicy and institutional reforms necessary to facilitate privatization, and develop management procedures for implementing privatization programmes successfully. - Reproduced
Keywords: Privatization - Latin America; Public sector - Latin America; Public sector; Privatization